Judges - Beldman, David J. H. (The Two Horizons Old Testament Commentary (THOTC) Ser., 2020)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- Theological Introduction -- Introduction to Judges -- The Title -- Hearing the Book of Judges -- Hearing Judges in Its Literary Context -- The Broad Context of Judges -- The Immediate Context of Judges -- Outline of Judges -- Hearing Judges as Hebrew Narrative -- Narrator -- Foolproof Composition -- Hearing Judges in Its Historical Context -- The Social Structure and Economy of Israel in Canaan -- The Land of Canaan -- The Religious and Cultural Environment of Israel in Canaan -- The Author, Audience, and Occasion of Judges -- Hearing Others Hearing Judges -- Early Christian/Jewish and Medieval Interpretation of Judges -- Renaissance and Reformation Interpretation of Judges -- Judges in Art, Music, and Theater -- Judges in the Late Modern Period and Beyond -- Judges and Modern Biblical Criticism -- Judges and the Literary Turn -- Judges and the Postmodern Turn -- Conclusion -- Theological Commentary -- The Exposition -- 1:1-2:5: Israel's Increasingly Unsuccessful "Mop-Up Campaign" -- 2:6-3:6: Israel's Rebellion and the Announcement of the Cycle -- The Cycle of Judges -- 3:7-11: The Othniel Cycle -- 3:12-30: The Ehud Cycle -- 3:31: Shamgar -- 4:1-24: The Deborah/Barak/Jael Narrative -- 5:1-31: The Song of Deborah -- 6:1-8:35: The Gideon Cycle -- 9:1-57: The Reign of Abimelech -- 10:1-5: Tola and Jair -- 10:6-12:7: The Jephthah Cycle -- 12:8-15: Ibzan, Elon, and Abdon -- 13:1-16:31: The Samson Cycle -- The End Section -- 17:1-18:31: Micah's Shrine and the Danite Migration and Conquest -- 19:1-21:25: The Atrocity at Gibeah and the Pan-Israelite War against Benjamin -- Retrospective Evaluation: A View of Judges from the End -- The Strategy of Completion -- The Strategy of Circularity -- The Strategy of Entrapment -- Summary and Conclusion.